Analisis SEMA No. 3 Tahun 2023 tentang Petunjuk bagi Hakim dalam Mengadili Perkara Permohonan Pencatatan Perkawinan Antarumat yang Berbeda Agama dan Kepercayaan: Perspektif Hukum Positif - Putri, Rizky Silvia (VISA: Journal of Vision and Ideas, 2024)
Marriage culture in Indonesia really reflects its diverse society, and the rules within it cannot be separated from the influence of religion, belief and knowledge of society. Registration of marriages of citizens of different religions has actually received recognition through Law Number 23 of 2006 in conjunction with Law Number 24 of 2013 concerning Population Administration. However, several judges have different interpretations regarding the Population Administration Law. This gives rise to disparities in judges' decisions in adjudicating cases of validating marriages between different religions. The Supreme Court issued SEMA Number 20 of 2023 as a guide for judges in adjudicating applications for registering marriages between people of different religions. So the author wants to see SEMA No. 3 of 2023 concerning Instructions for Judges in Adjudicating Applications for Registration of Marriages Between People of Different Religions and Beliefs from a positive legal perspective. This type of research is library research, there are also sources of information used, namely secondary information. The nature of this research is normative juridical. The results of this research are SEMA Number 20 of 2023 concerning Guidelines for Judges in Adjudicating Cases of Requests for Registration of Marriages Between People of Different Religions and Beliefs and are in line with the laws and regulations in Indonesia which are the reference for judges in determining the validity of a Marriage, including the 1945 Constitution of the Republic of Indonesia, Law -Marriage Law, Constitutional Court decision Number 68/PUU-XII/2014 and Number 24/PUU-XII/2022 as well as the religious values believed in by the Indonesian people.